Construction of Historical Memory through Youth Music: Example of the City of Kazan - Garifzianova, Albina Raisovna; Ozerova, Karina Adgamovna (Journal of History Culture and Art Research, 2019)
This article is devoted not only to how language, traditions and the past can serve as a creative resource for the creative activity of youth, but also about the ways music becomes a tool for social memory development by youth at the level of everyday life. In this article we want to consider how the historical memory of modern youth is actualized through cultural practices and interests. Actualization should be understood on the one hand, as referring to the themes of the past, not only to legitimize certain decisions of the state, social movements and public persons, but also to justify, with the help of the past, a certain assessment of current events and incitement to action. Also, a significant layer of research draws attention to the creation of symbolic objects (including music) to demonstrate the specific content of historical representations of various groups and those remembering practices that are relevant to them. Moreover, the level of these practices can be both organized, associated with the actions of formal institutions (the World Forum of Tatar Youth, for example), and relate to direct interaction between people at the everyday level - in our study the thing is about the latter.